Experimental study: correcting the calculation formula for a welded metal bellows' effective diameter. Issue 10 (October 2016) - Zhang, Xian; Ma, Yongmei; Zou, Hanyang; Tao, Shuai; Zhang, Qingcheng; Zhang, Erqing
Abstract : Calculation formulae for the effective diameter of bellows have been the subject of past studies, but very few of these have covered the calculation formula for the S-shaped welded metal bellows' effective diameter. This article describes research that looks at the effects of medium pressure on the S-shaped welded metal bellows' effective diameter, using an experimental set-up. Change rules of the effective diameter under different medium pressures were obtained and are discussed. By using curvilinear and linear regression methods, a new corrected calculation formula was obtained and its accuracy verified.